Applying In Dubio Pro Natura in Environmental Crime Cases: Legal Perspectives in Indonesia - Asmarani Ramli; Tegar Islami Putra; Natasya Fitri Dewanti; Salisa Widyaning Kinasih; Ridwan Arifin; Siti Hafsyah Idris (Universitas Negeri Semarang, 2023)
This research aims to analyze the application of the